241 Delayed onset of ventricular fibrillation after electrical injury in a young patient with asymptomatic mitral valve prolapse. (17th December 2020) - Benini, Annachiara; Ferri, Luisa; Marin, Federico; Gambaro, Alessia; Prati, Daniele
Abstract: Aims: The most frequent cardiovascular effects induced by electrical injury (EI) are arrhythmias, which occur mostly early after the electrical shock. A few cases of delayed malignant arrhythmias have been described, raising doubts about the helpfulness of heart monitoring after an EI. Methods and results: A 46-year-old man experienced an out-of-hospital cardiac arrest four hours after receiving an electrical shock with an alternating voltage of 380 volts from high-pressure water jet cleaner. The out-of-hospital ECG displayed ventricular fibrillation, eight DC shocks were delivered, and return of spontaneous circulation was obtained after 15 minutes. ECG on admission showed bradycardia, HR 55 b.p.m., no clear P waves and prominent T waves in the precordial leads (Figure A). No coronary lesions were detected at the urgent PCI. An ABG on admission revealed lactic acidosis (LAC 18 mmol/L), mild hyperkalaemia (5.19 mmol/L) and mild renal dysfunction (serum creatinine 1.71 mg/dL). Toxicology screen was negative. During the hospital stay, the patient developed a voluminous hematoma and swelling on the right arm, site of the EI. In the following days, blood tests revealed an increase in serum creatinine (peak 4.99 mg/dL), creatine kinase (peak 46186 U/L), liver enzymes (AST peak 2859 U/L and ALT peak 1365 U/L), LDH (peak 2718 U/L) and troponin T (peak 2757 ng/L); these alterations were probably linked to rhabdomyolysis provoked by EI and acute kidney injury was secondary to myoglobinuria. The patient received fluid therapy and furosemide bolus injections. On echocardiography a myxomatous mitral valve with prolapse of both leaflets, mitral annular disjunction and severe mitral regurgitation were displayed (Figure B). Left ventricle was severely dilated with ejection fraction 69%. After improvement in renal function, a cardiac MRI was performed, which ruled out myocardial oedema and displayed subendocardial LGE at the base of the posteromedial papillary muscle (Figure C). The Heart Team opted for mitral valve surgery with P2 resection and mitral valve annuloplasty with 36 mm Carpentier-Edwards Physio II Ring. An ICD was not implanted because the electrical shock and the alteration in electrolytes were considered the primary reasons for cardiac arrest. The patient underwent a cycle of rehabilitation after the intervention and now he does not report any relevant symptom. Conclusion: Our patient had bileaflet mitral valve prolapse, mitral annular disjunction and myocardial fibrosis of the papillary muscles, all of which are associated with higher risk of sudden cardiac death. This case highlights that patients with an underlying heart condition predisposing to arrhythmias should promptly seek medical care even after a mild EI for appropriate management.